1995
DOI: 10.2527/1995.7382390x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth rate on carcass composition and lipid partitioning at puberty and growth hormone, insulin-like growth factor I, insulin, and metabolites before puberty in beef heifers2

Abstract: The effect of three rates of gain on carcass composition, lipid partitioning, age and BW at puberty, and concentrations of growth hormone (GH), IGF-I, insulin, glucose, and NEFA in plasma were evaluated in 38 Angus x Hereford heifers. Heifers were allotted by BW and age to three treatments with a replication in each of 2 yr: full-fed (n = 13; FF) to gain 1.36 kg/d; limit-fed (n = 12; LF) to gain .68 kg/d; maintenance-full-fed (n = 13; MFF) to gain .23 kg/d for 16 wk, then full-fed to gain 1.36 kg/d. Heifers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
2
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 0 publications
9
34
2
6
Order By: Relevance
“…This is in contrast with an older theory that a heifer needs to reach a specific level of somatic development (BW) for the onset of puberty to be induced (Day et al, 1984(Day et al, , 1987Foster, 1994) and may indicate that there is Reproductive tract scoring in beef heifers an age-related induction of puberty that is not related to the BW of the heifer, in agreement with Yelich et al (1995) and Pence et al (2007). On the other hand, it may also indicate some variation in the critical BW of individual heifers that needed to be achieved to induce puberty, meaning that there was some scope for selection for AP in this population.…”
Section: Discussioncontrasting
confidence: 53%
“…This is in contrast with an older theory that a heifer needs to reach a specific level of somatic development (BW) for the onset of puberty to be induced (Day et al, 1984(Day et al, , 1987Foster, 1994) and may indicate that there is Reproductive tract scoring in beef heifers an age-related induction of puberty that is not related to the BW of the heifer, in agreement with Yelich et al (1995) and Pence et al (2007). On the other hand, it may also indicate some variation in the critical BW of individual heifers that needed to be achieved to induce puberty, meaning that there was some scope for selection for AP in this population.…”
Section: Discussioncontrasting
confidence: 53%
“…Some authors observed that females became pubertal with a greater weight and BCS when subjected to a high-energy diet (Pattherson et al, 1990;Hopper et al, 1993;Yelich et al, 1995). In the present study, LMA was increased by high energy intake as was the cold carcass weight.…”
Section: Discussionsupporting
confidence: 64%
“…The lack of treatment effects on plasma insulin on day 51 was unexpected because circulating insulin is also positively regulated by nutrient intake and glucose concentrations (Vizcarra et al, 1998). On the other hand, the greater plasma insulin concentration in CON heifers on days 261 and 325 support treatment trends (P = 0.09) detected on ADG during the development phase (Table 3), corroborating that CON heifers had more dietary nutrients available for growth during this period (Yelich et al, 1995;Hess et al, 2005). No treatment effects were detected (P = 0.35) on plasma leptin concentrations (Table 5), although circulating leptin concentration is regulated by nutrient intake and insulin (Houseknecht et al, 1998).…”
Section: Physiological Variablesmentioning
confidence: 78%